Perlindungan Hukum Terhadap Pasien Pengguna BPJS Kesehatan Di Rumah Sakit - Dewinta Widianingtyas (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Health BPJS program aims to provide assurance of social protection and welfare for all Indonesian people. One of the problems that patients who use BPJS often face is the problem of Health BPJS services in the field, namely cases of refusal of patients participating in Health BPJS to get an examination room by the hospital. The need for legal protection in obtaining health services, which aims to ensure legal certainty obtained by patients that patients avoid losses when receiving health services that should be provided properly and optimally by health workers. This study aimed to identify and analyze the legal protection of patients who used Health BPJS in hospitals. This study used a normative juridical approach. The result showed that there were two kinds of legal protection for Health BPJS participants in health services, namely preventive and repressive legal protection.